Study of effective removal of nickel and cobalt from aqueous solutions by FeO@mSiO2 nanocomposite - Wahran M. Saod; Nisreen Jassam Alaallah; Ekhlas A. Abdulkareem; Nahla Naji Hilal; Mohammad I. AlBiajawi (Results in Chemistry)
In many regions of the world, water pollution from potentially harmful substances like nickel (II) and cobalt (II) ions is a recurring issue. The quality of rivers and lakes’ environments, wastewater discharge, and drinking water sources are all still significantly impacted by it. Many studies are focused on developing new treatment alternatives since, although treatment is often necessary, it is not always possible or accessible in a particular setting. Nanotechnology provides significant potential for water treatment. Although it has been demonstrated that nanomaterials may effectively remove both different type from chemical pollutants—including organic and inorganic—from contaminated source, their removal efficacy may be diminished by their propensity to flocculate. Iron oxide loaded with mesoporous silica (FeO@mSiO2) was effectively synthesized and characterized through the use of FTIR, SEM, TGA, XRD, and UV–visible spectral analysis. Tests and evaluations were conducted to determine FeO@mSiO2 nanocomposite ability to remove nickel (II) and cobalt (II) from solution, and the ideal removal conditions were determined at different condition Adsorption isotherms, Freundlich and Temkin isotherms to the data. FeO@mSiO2 composite material displayed significant efficacy in the removal of Ni and Co. The best removal rates were attained at pH 7 and 180-minute contact duration.